Rules for second chances - North, Maggie (St. Martin's Griffin, 2024)
"Brimming with heart and heat, Rules for Second Chances explores the hardest relationship question of all: can true love happen twice...with the same person? Liz Lewis has tried everything to be what people want. But she's always been labeled different from everyone else in the boisterous world of wilderness expeditions--that is, if anyone notices her at all. Her marriage to popular adventure guide Tobin Renner-Lewis is a sinkhole of toxic positivity where she's the only one saying no. In a mountain resort town built around excitement, introverted Liz gets...spreadsheets. When she gets mistaken for a server at her own thirtieth birthday party and her last line of communication with Tobin finally snaps, Liz vows to stop playing a minor character in her own life. The (incredibly well-researched and scientific) plan? A crash course in confidence...via improv comedy class. The catch? She's terrible at it, and the only person willing to practice with her is a certain extroverted wilderness guide who seems dead set on saving their marriage one bonkers improv scenario at a time. But as Liz and Tobin get closer (...again), she's forced to confront all the reasons they didn't work the first time, along with her growing suspicion that there might be more to her social awkwardness than anyone realized. Liz has just eight weeks to learn improv's most important lesson--"yes, and"--or she'll have to choose between the love she always wanted and the dreams that got away"--